Factors associated with dietary adherence to the guidelines for prevention and treatment of hypertension among Korean adults with and without hypertension - Jee-Seon Shim; Ji Eun Heo; Hyeon Chang Kim (BMC, 2020)
Abstract Background Although dietary modification is strongly recommended for prevention and treatment of hypertension, little is known about which factors are associated with adherence to dietary guidelines. We investigated knowledge and attitude, perceived benefits of, barriers to, and self-efficacy of dietary therapy, and identified the factors associated with dietary adherence among adults with and without hypertension. Methods We collected information on the knowledge/attitudes and perceived benefits of dietary therapy, as well as barriers to and self-efficacy regarding dietary adherence from 497 middle-aged (34-69 years) adults who participated in the follow-up examination of the Cardiovascular and Metabolic Diseases Etiology Center (CMERC) cohort study during December 2018 and February 2019. Results Among people without hypertension, 95.5% (343/359) and 95.8% (344/359) answered that they would limit sodium intake and consume health diet, respectively, if diagnosed hypertension. However, among people with hypertension, only 79.7% (110/138) and 77.5% (107/138) reported they were limiting dietary sodium intake and having healthy diet, respectively. Frequency of diet management was not different between normotensive (34.0%) and hypertensive (35.5%) groups. Compared to normotensives, hypertensive people were more likely to have lower dietary adherence score, think they need to change their diet, think dietary change impossible, and report lower self-efficacy for following diet guidelines. Dietary management was significantly associated with cardiometabolic risk factors (OR: 1.63) and dietary education (OR: 2.19) among normotensives, while it was associated only with awareness that lifestyle modification is necessary regardless of antihypertensive medication (OR: 6.29) among hypertensive people. Good dietary adherence had significant associations with perceived barriers (OR: 0.71), self-efficacy (OR: 3.71), and dietary education (OR: 1.98) among normotensives; and with perceived barriers (OR: 0.54), self-efficacy (OR: 4.06), and dietary management (OR: 4.16) among hypertensive people. Conclusions Many Koreans have relatively low adherence to dietary guidelines for hypertension prevention and treatment. Knowledge, dietary practices, and factors affecting dietary adherence were different between adults with and without hypertension. A targeted approach will be needed to improve blood pressure control of the Korean population.